Surgical Management of Primary Bone Lymphoma of the Hip: A Case Report and Review of the Literature - Grace Kennedy; Phil Weir; Kevin Johnston; Patrick Elder (Case Reports in Orthopedics)
Introduction. Primary bone lymphoma (PBL) is a rare bone malignancy which may present with atraumatic pain, swelling, or pathological fracture. Whilst the femur is the most commonly affected site, any bone may be involved. PBL should be distinguished from other bone lesions to determine clinical management. Case Report. We report the case of an 89-year-old gentleman who presented to the local emergency department with atraumatic hip pain and inability to weight-bear. Multimodal imaging showed evidence of a tumor involving the proximal femur and adjacent acetabulum with an associated pathological intertrochanteric fracture. Biopsy specimens demonstrated this to be PBL of the diffuse large B-cell subtype. No other disease foci or nodal involvement was identified. The patient underwent proximal femoral replacement and acetabular reconstruction prior to commencing R-Mini-CHOP chemotherapy, during which time he has been permitted to fully weight-bear. Conclusion. To our knowledge, this is the first reported case of a patient having PBL with both femoral and acetabular involvements. Due to its infrequent occurrence, evidence remains limited to advise therapeutic guidelines. Our practice concurs with literature suggesting that surgery be reserved for cases of pathological fracture. However, the merits of undergoing surgical fixation prior to chemoradiation treatment have been considered.